Effect of oestrus cervical mucus peroxidase and fern pattern on fertility in crossbred cows - SRIVASTAVA, S K; SHANKER, UMA; AGARWAL, S K; SAHNI, K L (The Indian Journal of Animal Sciences, 2014)
Cervical mucus peroxidase activity and ferning pattern was studied in 60 crossbred cows at the AI, Typical (63.33%),atypical (26.67%) and nil (10.00%) types of pattern were observed. After insemination and pregnancy diagnosis 55.26%and 18.77% cows became pregnant with typical and atypical types of patterns which were significantly different (P